Effect of Foreign Commissioners, Ethnic Commissioners, Feminism Commissioners Towards CSR Disclosure - Anita Ade Rahma; Febri Aldi (Universitas PGRI Madiun, 2020)
ABSTRACTThe study aims to test whether the foreign commissioners, ethnic commissioners, and feminism commissioners influence CSR disclosure. This study used a sample of 20 companies LQ-45 are listed on the Stock Exchange from 2015 to 2017. CSR disclosure using the GRI-G4 standard. Ethnic commissioners focused on the presence of ethnic Chinese. The results of this study prove that the foreign commissioners’ variables did not affect CSR disclosure. While on the contrary, ethnic commissioners and feminism commissioners gave a positive effect on CSR disclosure. The existence of ethnic Chinese in the board profitable companies to improve disclosure of CSR index. Likewise, the role of women is needed for the breadth of CSR disclosure.ABSTRAKPenelitian bertujuan untuk menguji apakah dewan komisaris asing, etnis dewan komisaris, dan feminism dewan komisaris mempengaruhi CSR dislosure. Penelitian ini menggunakan sampel 20 perusahaan LQ-45 yang terdaftar di BEI dari 2015-2017. CSR disclosure menggunakan GRI-G4 standard. Etnis dewan komisaris terfokus pada keberadaan etnis Cina. Adapun Hasil penelitian ini membuktikan bahwa variabel dewan komisaris asing tidak berpengaruh terhadap CSR disclosure. Sedangkan sebaliknya, etnis dewan komisaris dan feminism dewan komisaris memberikan pengaruh yang positif terhadap CSR disclosure. Keberadaan etnis Cina dalam dewan menguntungkan perusahaan untuk meningkatkan index CSR disclosure. Begitu juga peran wanita sangat dibutuhkan demi luasnya CSR disclosure.